Relação da potência aeróbica máxima e da força muscular com a economia de corrida em atletas de endurance - Guglielmo, Luiz Guilherme Antonacci [UNESP]; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (FapUNIFESP (SciELO), 2005)
The objective of this study was to analyze the relationship of maximal aerobic power and the muscular strength (maximal isotonic strength and vertical jump explosive power) with the running economy (RE) in endurance athletes. Twenty-six male runners (27.9 ± 6.4 years; 62.7 ± 4.3 kg; 168.6 ± 6.1 cm; 6.6 ± 3.1% of body fat) performed in different days the following tests: a) incremental test to determine the maximal oxygen uptake (V̇O2max) and the intensity corresponding to the V̇O2max (IV̇O2max); b) constant-velocity treadmill run to determine RE; c) 1-RM test in the leg press and; d) maximal vertical jump test (VJ). V̇O2max (63.8 ± 8.3 ml/kg/min) was significantly correlated (r = 0.63; p < 0.05) with RE (48.0 ± 6.6 ml/kg/min). However, the IV̇O2max (18.7 ± 1.1 km/h), the maximal isotonic strength (230.3 ± 41.2 kg) and the VJ (30.8 ± 3.8 cm) were not significantly correlated with RE. One concludes that the maximal aerobic power can explain in part the inter-individual RE variability in endurance athletes. However, maximal isotonic strength and explosive strength seem not to be associated with RE values observed in this group of athletes.
Relationship of maximal aerobic power and muscular strength with the running economy in endurance athletes
Keywords: Maxiamal oxygen uptake; Muscular strength; Running economy; aerobic capacity; anthropometry; athlete; correlation coefficient; human; human experiment; male; muscle isotonic contraction; muscle strength; normal human; oxygen consumption; physical capacity; physical stress; running; statistical analysis; statistical significance; treadmill exercise